2020
DOI: 10.21873/anticanres.14221
|View full text |Cite
|
Sign up to set email alerts
|

A Triple-negative Matrix-producing Breast Carcinoma Patient-derived Orthotopic Xenograft (PDOX) Mouse Model Is Sensitive to Bevacizumab and Vinorelbine, Regressed by Eribulin and Resistant to Olaparib

Abstract: Background/Aim: Matrix-producing breast carcinoma (MPBC) is a rare and usually aggressive triplenegative breast cancer (TNBC). In this study, we determined drug sensitivity for a triple-negative MPBC, without BRCA mutations, in a patient-derived orthotopic xenograft (PDOX) model. Materials and Methods: The MPBC PDOX model was established in the left 2 nd mammary gland of nude mouse by implantation of the patient tumor using surgical orthotopic implantation (SOI). We randomized MPBC PDOX mice into 5 groups (n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The future goal is to use the new method of patient-tumor transplantation to enable universal individualized therapy for cancer patients, such that each cancer patient has their own mouse tumor model to help identify improved therapy. The results of the present study show that high tumor stage and the presence of metastasis in the patient increased the probability of tumor engraftment in nude mice, suggesting that the patients in greatest need will have the best chance for identification of more effective therapy with a mouse model of their tumor, especially the PDOX model, which mimics the patient (4,(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The future goal is to use the new method of patient-tumor transplantation to enable universal individualized therapy for cancer patients, such that each cancer patient has their own mouse tumor model to help identify improved therapy. The results of the present study show that high tumor stage and the presence of metastasis in the patient increased the probability of tumor engraftment in nude mice, suggesting that the patients in greatest need will have the best chance for identification of more effective therapy with a mouse model of their tumor, especially the PDOX model, which mimics the patient (4,(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 70%
“…Individualized cancer therapy currently uses genome analysis (5), drug-sensitivity testing with 3-D culture of tumor in vivo 34: 3241-3245 (2020) fragments (6)(7)(8)(9) or organoids (10,11) as well as patientderived xenograft (PDX) or, patient-derived orthotopic xenograft (PDOX) models (12)(13)(14)(15)(16). Genome analysis has helped only a limited number of cancer patients identify effective drugs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel effective therapy is urgently needed for MPBC patients. Our previous studies of triplenegative MPBC PDOX, showed eribulin was effective (12,13).…”
Section: Discussionmentioning
confidence: 97%
“…We have previously demonstrated that the PDOX model retains the histopathological/molecular and metastatic characteristics of the original tumor after SOI in 5 mice (9-11). We previously showed eribulin regressed triple-negative MPBC PDOX mouse models (12,13).…”
Section: Introductionmentioning
confidence: 97%
“…Recent developments in the patient derived xenograft (PDX) model seem capable of producing samples that are authentic to the host tumor, which replicate tumor growth, tumor diversity, and tumor progression, including metastatic potential [ 171 ]. Furthermore, in patients with TNBC, several applications of PDX models have been made in terms of drug screening [ 172 , 173 , 174 , 175 , 176 ], drug resistance profiling [ 177 ], prognostic and functional gene assessment [ 178 , 179 ], and metastatic assessment [ 180 , 181 ]. In the future, PDX models may become the trend in personalized therapy and minimize the need for expensive and prolonged randomized controlled trials.…”
Section: Patient Derived Xenograft Model: a Solution To The Diversmentioning
confidence: 99%